FEASIBILITY STUDY OF 3D PRINTING METHOD IN SCAFFOLD FABRICATION FOR FEMUR BONE IMPLANT APPLICATION IN INDONESIA - Arzan Marzuqi, Muhammad
Bones are rigid and hard organs that form the human skeleton. Additionally, bones serve various functions, including providing support and creating the structure of the human body, protecting vulnerable vital organs, facilitating respiration, and producing red and white blood cells. Damage to bone tissue, such as fractures or osteoporosis, it can lead to a decline in the quality of human life. The demand for bone implants (osteosynthesis) in Indonesia reaches 100,000 per year, with 90% of this prosthetic demand being fulfilled through imports. However, there are shortcomings in using imported bone implants, such as higher cost and lack of compatibility with the shorter bones of the indonesian population, resulting in suboptimal medical treatment [1]. The development of scaffolds for bone implants is a novel application of smart biomaterials that presents a compelling solution to address femur bone implant challenges in Indonesia. This is because scaffolds can enhance cell growth and bone tissue regeneration processes. To ensure optimal outcomes from the created scaffolds, design with accurate and precise dimensions is essential to support cell adhesion, proliferation, and differentiation. One effective approach to achieve this is by utilizing 3D printing methods (technology). This feasibility study encompasses an analysis of the internal and external environments influencing a 3D printing company specializing in the production of femur bone scaffolds for implants in Indonesia. Internal environmental identification is conducted using VRIO analysis, while external environmental identification employs PESTEL and Porter’s Five Forces analysis. Subsequently, the appropriate type of 3D printer and suitable materials for the 3D scaffold printing application are determined. This determination is achieved through the use of a weighted decision matrix method with direct weighting. Following this, investment costs (CAPEX) and operational costs (OPEX) are calculated. Finally, financial analysis is conducted by creating cash flow projections and assessing investment feasibility through NPV (Net Present Value), IRR (Internal Rate of Return), BEP (Break Even Point), POT (Payback Period), and PI (Profitability Index) criteria. All feasibility study analyses are conducted within specific geographical constraints in Indonesia. The feasibility study will ascertain whether the application of 3D printing method for the fabrication of femur bone implant scaffolds is feasible in Indonesia.